APLIKASI PEMBELAJARAN MATEMATIKA BERBASIS ANDROID UNTUK SLOW LERANER PADA MATERI ALJABAR - Lulu Farida; Mety Liesdiani (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The purpose of this research is to develop and produce a learning media in the form of an Android-based learning application for algebra material for slow learners, using multisensory concepts, visual methods, and realistic algebra concepts The aim of this study is to assist the learning process of slow learner students in inclusive school using a new medium, namely the Android-based learning application In order to not only use conventional learning, because in the learning process, but slow learners also need specific additional methods and media to help them understand each taught material The method used in this research is the Research And Development (R&D) method using the ADDIE development model. The data collection technique used is validation sheets, while the data analysis technique used in this research is primary data Based on the research results, it is shown that the Android-based mathematics learning application for slow learners in algebra material meets valid criteria. The overall score for each statement on the validation sheet is 100%, with the category very valid, so the learning application can used in the learning process.